Characterization of Sandia Capacitive Comb-finger MEMS Accelerometers - Joshi, Aaditi; Redkar, Sangram; Sugar, Thomas (Institute of Advanced Engineering and Science, 2015)
This paper discusses various methods for testing the performance of MEMS capacitive comb-finger accelerometers manufactured by Sandia National Laboratories. The use of Capacitive MEMS devices requires complex circuits for measurement of capacitance and the Sandia MEMS accelerometerâs capacitance changes in a very small femto-farad (fF) range. The performance of accelerometer is tested using Analog Devices AD7747 sigma-delta capacitance to digital converter. The response of a MEMS capacitive accelerometer to various tests is useful for testing and characterization and investigate itâs suitability for various applications.